2016
DOI: 10.21037/atm.2016.12.45
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers for radiosensitivity in head and neck cancers

Abstract: Radiotherapy is a mainstay of treatment for head and neck cancer. However, the morbidity of treatment remains a clinical challenge. Molecular profiling has provided further insight into tumor biology and tumor sensitivity to radiation, and this information could be used to personalize treatment. In this review, we discuss published signatures of radiosensitivity and discuss the pathways that may be important in dictating radiation sensitivity. Applications of these signatures could result in less morbidity if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Identification of deregulated proteins could be applied clinically in terms of either radioresistance-associated biomarkers or as potential targets for radiosensitization. These novel biomarkers related to either radiosensitivity or radioresistance would permit improved stratification of HNSCC patients based on the predicted response to irradiation [69]. Radiosensitization of more radioresistant tumors could also lead to reduced total irradiation dose, fewer and/or milder adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of deregulated proteins could be applied clinically in terms of either radioresistance-associated biomarkers or as potential targets for radiosensitization. These novel biomarkers related to either radiosensitivity or radioresistance would permit improved stratification of HNSCC patients based on the predicted response to irradiation [69]. Radiosensitization of more radioresistant tumors could also lead to reduced total irradiation dose, fewer and/or milder adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that various immune parameters are related to radiosensitivity, and that the CD8 + T cell or Treg population plays an important role in the antitumor effect of RT 28‐31,37 . In the present study, we investigated the association between LC and TIL status, PD‐L1 expression, and their combination on the tumor radiosensitivity of 91 patients with SCC‐L who had undergone a definitive RT.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies reported that various immune parameters are related to radiosensitivity, and that the CD8 + T cell or Treg population plays an important role in the antitumor effect of RT. [28][29][30][31]37 In the present study, we investigated the association between LC and TIL status, PD-L1 expression, and their combination on the tumor radiosensitivity of 91 patients with SCC-L who had undergone a definitive RT. Using multivariate analysis, we found that CD8/FOXP3 ratio, but not CD8+, CD4+, nor FOXP3 TIL density; PD-L1 expression; and CD8/CD4 ratio showed significant association with LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor radiosensitivity may also influence the effect of TTI on outcome. While to some extent it may be evaluated before RT begins (e.g., by molecular profiling, identification of hypoxic cells, and the determination of HPV status in oropharyngeal primary tumors), in daily clinical practice it is usually not considered when planning treatment [45,46]. In order to diminish the impact of intrinsic tumor radiosensitivity, the patients in our study with residual disease at 10-12 weeks post-RT were excluded from the analysis of LRC.…”
Section: Discussionmentioning
confidence: 99%